Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Syzygium australe leaves and fruit. Syzygiumis a large genus of evergreen flowering plants of the family Myrtaceae which consists of approximately 500 species. Plants of this genus are widespread, occurring in tropical and subtropical regions of South-East Asia, Australia and Africa. Many Syzygium species produce edible fruits and berries (eg. Syzygium jambos, commonly known as rose apple). In the commercially most important species Syzygium aromaticum (clove), the unopened flower bud is used as a spice. This plant also has uses in traditional medicine due to its anaesthetic properties.1 The antimicrobial activity of S. aromaticumis also well known. Numerous studies have reported on the antibacterial2 and antifungal3 activities of oils and extracts from this plant. Other Syzygium species from Africa4-6 South East Asia (Syzygium jambos),7 India (Syzygium lineare and Syzygium cumini)8 and Australia9-13 have also been shown to have antimicrobial activity. Recent reports have also highlighted Syzygium australe (Bush Cherry) and Syzygium leuhmannii (Riberry) extracts as having exceptionally high antioxidant contents.14, 15Antioxidants have been associated with the prevention of cancer, cardiovascular disease and neurological degenerative disorders.16-19 They are also linked with anti-diabetic bioactivities and have been associated with the reduction of obesity. Antioxidants can directly scavenge free radicals, protecting cells against oxidative stress related damage to proteins, lipids and nucleic acids.19 Thus the Syzygiums have potential in the treatment of a significant number of diseases and medical conditions related to cellular redox state. This photograph was taken in Brisbane, Australia in 2015 by Dr Ian Cock.